1974
DOI: 10.1172/jci107785
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid-Stimulating Activity and Chorionic Gonadotropin

Abstract: The nature of the substance with thyroid-stimulating activity (TSA) present in human chorionic gonadotropin (hCG) prepared from pregnancy urine was investigated. In the mouse thyrotropin bioassay, the characteristic maximum of blood radioactivity obtained with the TSA in hCG preparations occurred after that obtained with pituitary thyrotropin (hTSH) but before that obtained with long-acting thyroid stimulator. Antiserum to the a subunit of hCG produced significant neutralization of the TSA in hCG. Significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
1

Year Published

1979
1979
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(15 citation statements)
references
References 32 publications
0
14
0
1
Order By: Relevance
“…This 'hyperthyroidism with suppressed TSH' is known with patients suffering Graves' disease, hyperemesis gravidarum, and trophoblastic diseases. The pathogenic agents causing these diseases have been identified: thyroid-stimulating antibodies in Graves' disease, excess levels of human chorionic gonadotropin (hCG) and in hyperemesis gravidarum (Lao et al 1988, Rodien et al 1998 and in trophoblastic diseases (Nisula & -Ketelslegers 1974, Nisula & Taliadouros 1980, Hoermann et al 1994. Recently, two cases of goitrous euthyroid patients presenting low TSH have been reported (Ikekubo et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This 'hyperthyroidism with suppressed TSH' is known with patients suffering Graves' disease, hyperemesis gravidarum, and trophoblastic diseases. The pathogenic agents causing these diseases have been identified: thyroid-stimulating antibodies in Graves' disease, excess levels of human chorionic gonadotropin (hCG) and in hyperemesis gravidarum (Lao et al 1988, Rodien et al 1998 and in trophoblastic diseases (Nisula & -Ketelslegers 1974, Nisula & Taliadouros 1980, Hoermann et al 1994. Recently, two cases of goitrous euthyroid patients presenting low TSH have been reported (Ikekubo et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Abundant reports now exist confirming the intrinsic thyroid-stimulating activity of the hCG molecule (1,21,22). hCG has activity in the mouse TSH bioassay (1,21,22), increases cAMP in human thyroid tissue (23), and displaces labeled TSH from the thyroid receptor in human and bovine thyroid tissue (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…In mammals thyroidgonadotropin hormone interaction is well documented (e.g. Nisula & Ketelsleger 1974, Nisula et al 1974, Amir et al 1977, Aranda et al 1976). Studies in a number of teleostean species have shown an apparent thyrotropic effect of mammalian or piscine gonadotropin preparations (Ahsan & Hoar 1963, Fontaine 1969b, Donaldson & McBride 1974, Grau & Stetson 1977a, Miline & Leatherland 1979, 1980b.…”
mentioning
confidence: 99%